When ‘Law’ Rhymes with ‘Flaw’: the Sounds of British Justice in Gilbert and Sullivan’s Trial by Jury (1875) - Joël Richard (Cahiers Victoriens et Edouardiens)
Gilbert and Sullivan’s second operatic collaboration, Trial by Jury (1875) is often discarded as a ‘minor’ work, compared to their later, better-known operas such as The Pirates of Penzance (1879), The Mikado (1885) or The Gondoliers (1889). Yet I would argue that as early as the mid-1870s, the composer-and-librettist duo had successfully started working on what might be perceived by their audience as the ‘sound’ best fit to satirize a number of Victorian institutions—here, the judicial system, turned topsy-turvy by a banal breach of promise case. Their already clever play on tessitura, the many echoes of grand Italian opera tunes and their attempt at rendering the comical and ludicrous atmosphere of the courtroom all coalesced to make Trial by Jury a key example of how both their witty words and catchy notes were—back then and are still now—heard as truly British.